Product Safety and Harm-Mitigation Incentives When Mitigation Lowers Consumption Benefits. (3rd September 2020) - Baumann, Florian; Friehe, Tim
Abstract: To reduce the expected harm its product causes to consumers, a firm can invest in a product's safety before sale or mitigate harm after sale in the event product risks materialize. After-sale harm mitigation interferes with consumers' product use and reduces consumption benefits. We describe a firm's incentives for safety investments and harm mitigation as a function of the level of the firm's liability. Whereas post-sale mitigation incentives are scaled up by liability, pre-sale product safety is a U-shaped function of liability, making the two harm reduction instruments substitutes at low levels of liability and complements at high levels. To induce efficient harm mitigation, liability must be less than full. Further reducing the level of liability improves product safety at the cost of the firm's profits. ( JEL K13, D42).